Strategies to reduce the brightness reversion of industrial ECF bleached Eucalyptus globulus kraft pulp - Sêco, Isabel M. C. L.
BACKGROUND: Brightness stability is a key property of bleached chemical pulps and is primarily determined by wood species and bleaching process conditions. Eucalyptus globulus is becoming a very important raw material for hardwood pulp production. In spite of this importance, there is a relative lack of systematic studies in the literature dealing with the subject. This research aims to study the effect of some of the foremost bleaching parameters of a DEDD bleaching sequence as well as the effect of a final P stage (DEDP instead of DEDD) in the brightness stability of bleached E. globulus kraft pulps. RESULTS: The increase of the Do stage temperature from 55 degrees C to 90 degrees C caused an increase in brightness stability. Increasing the ClO2 charges from 2.8% to 3.2% also improved significantly the brightness stability. A high H2SO4 charge in the D-0 stage (10 kg tonne(-1) pulp) diminished the brightness stability. The combination of H2O2 addition to the E stage and ClO2 reduction in the two final D stages does not affect brightness reversion. Raising the D-2 stage temperature from 65 degrees C to 82 degrees C decreased the brightness reversion, while an increase was obtained when the temperature rose above 82 degrees C. Substitution of the last ClO2 stage in the DEDD sequence by a H2O2 stage (DEDP) significantly reduced the brightness reversion. CONCLUSION: For an existing pulp mill in which the implementation of new technologies to improve brightness reversion is considered, the results obtained showed that brightness stability can be improved without any significant capital investment. (C) 2007 Society of Chemical Industry.